Pengembangan Batik dan Kreasi Batik Sebagai Ekstakurikuler Unggulan SD Kuncup Melati Semarang - Florentina Irena Ristamadi; Alexander Agung Satrio; Maria Gheavari Nindya; Fanny Freshinaya; Martha Widiana Mayangsari; Meniek Srining Prapti; Ch. Yekti Prawihatmi (Universitas Katolik Soegijapranata, 2019)
Extracurricular activities outside of school hours, aiming to develop student;s interests and talents. SD Kuncup Melati has extracurricular activities,namely batik (batik jumputan), which is intended for students in grades 5 and 6. Efforts to improve extracurricular batik by mentoring and training by Unika Soegijapranata through Kuliah Kerja Usaha (KKU) activities. KKU activities involve lecturers, students, and school participation (students and teachers). The program of KKU’s acticities is to develop and add shibori batik motifs, making creative accesories from batik. The results of KKU’s activities are the batik motif that are increased in the form shibori batik with various models, and creative batik necklaces and key chains. From this activities, batik’s extracurricular and accessory batik’s creation are to be the main activities of SD Kuncup Melati